Effects of Annular Combustor Width on the Ethylene-Air Continuous Rotating Detonation. (14th September 2020) - Fan, Weijie; Liu, Shijie; Zhou, Jin; Peng, Haoyang; Huang, Siyuan
Abstract : The realization and stable operation of Continuous Rotating Detonation (CRD) in the annular combustor fueled by hydrocarbon-air are still challenging. For further investigation of this issue, a series of ethylene-air CRD tests with the variation of combustor width is conducted, and the effects of combustor width are well analyzed based on high-frequency pressure and high-speed photograph images. The results show that the combustor width plays a significant role in the realization and sustainability of the ethylene-air CRD. In this paper, the critical combustor width for the CRD realization and stable single wave are 20 mm and 25 mm, respectively. In wide combustors, the backward-facing step at the combustor forepart makes the main flow slow down, and thus, the mixing quality is promoted. Besides, the pilot flame at the recirculation zone contributes to sustaining the CRD wave. As the width increases, the propagation mode changes from counter-rotating two-wave mode to single wave mode with higher propagation velocity and stability. The highest propagation velocity reaches 1325.56 m/s in the 40 mm wide combustor, accounting for 71.51% of the corresponding Chapman-Jouguet velocity. Despite large combustor volume, high combustor pressure is obtained in detonation combustion mode indicating that a better propulsive performance could be achieved by CRD.